H2O2/UV-C Treatment of the Economically Important Naphthalene Sulfonate J-Acid: Process Optimization, Kinetic Evaluation and Activated Sludge Inhibition - Arslan-Alaton, Idil; Olmez-Hanci, Tugba; Kartal, Zeynep (Sycamore Global Publications, 2010)
AbstractJ-acid (2-amino-5-naphthol-7-sulfonic acid) is an economically important naphthalene sulfonate having a highly polar, aromatic structure that renders it a difficult-to-oxidize, coagulate or adsorb pollutant. In the present study, the treatability of aqueous J-acid employing H2O2/UV-C oxidation and the effect of H